DISSOLVED SILICATE IN COASTAL WATER OF SOUTH SULAWESI - Muhammad Lukman; Andriani Nasir; Khairul Amri; Rahmadi Tambaru; Muhammad Hatta; Nurfadilah Nurfadilah; Rahmat Januar Noer (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
ABSTRACT Dissolved silicate (DSi) in coastal waters plays a crucial role in phytoplankton growth particularly diatom. This study aimed to determine DSi concentration seasonally in waters of the western coast of South Sulawesi in relation to coastal water quality indicator. Water, chlorophyll-a, and diatom samples were collected from the coastal areas of the Tallo-Makassar, Maros, and Pangkep, in April 2013 (transitional season), June 2013 (dry season), and February 2014 (wet season). Factorial analysis of variance was used to identify significant seasonal and temporal variations, and linear regression was used to test the relationship of chlorophyll-a and diatom abundance to DSi concentrations. The results showed that the DSi concentration was higher in the wet season of 35.2-85.2 µM than in the other seasons (transitional season: 10.8-68.4 µM, dry season: 9.59-24.1 µM). The abundance of diatoms during the transitional season reached 9.7x107 cell/m3 in the Pangkep river, 2.3x107 cell/m3 in the Tallo river, and 1.3 x 107 cell/m3 in the Maros river. Chaetoceros, Nitzschia, and Rhizosolenia dominated the diatom composition. The mean concentration of chlorophyll-a in the Makassar coastal waters was 4.52±4.66 mg/m3, while in the Maros and Pangkep waters of 1.40±1.06, and 2.72±1.94 mg/m3, respectively. There was no strong linear corelation between DSi and diatom abundances, nor chlorophyll-a. These results suggested that DSi become a non-limiting factor for the diatom growth and potentially reduce the water quality via eutrophication and diatom blooms. Keywords: dissolved silicate, diatom, chlorophyll-a, coastal waters, South Sulawesi